Herstellung von Polyestern durch ringöffnende, ionische Copolymerisation von Dicarbonsäureanhydriden und Ringäthern - Karl-Heinz W. Reichert (CHIMIA)
For the preparation of polyesters an ionically initiated ring-opening copolymerization reaction of dicarboxylic acid anhydrides and cyclic ethers can be used beside the conventional polycondensation technique. The main advantage of this copolymerization reaction with respect to the polycondensation is, that higher molecular weights can be obtained (up to 100000) with this method. Using anionic initiators, e.g. carboxylates, polyesters from three- and four-membered cyclic ethers and cyclic anhydrides can be prepared whereas with cationic initiators, e.g. with PF5 or with triethyloxoniumfluoroborate, cyclic ethers of any ring size are copolymerizable with dicarboxylic acid anhydrides. With anionic initiation an alternating arrangement of the comonomers along the chain was pointed out, whereas from cationic copolymerization polyesters with ether groups in the polymer backbone were established, even above the ceiling temperature of the cyclic ether. From chemical degradation experiments and from spectroscopic investigations the ether/ester ratio of these copolymers was ascertained. This ratio, which is a quantity of the relative reactivity of the comonomers was compared with spectroscopically obtained structural data of the monomers. Furthermore investigations on the pathway and the mechanism of the ringopening copolymerization were carried out. On both the anionic and the cationic reaction a living character of the copolymers could be observed.